miR-17-5p and miR-4443 Promote Esophageal Squamous Cell Carcinoma Development by Targeting TIMP2 - Wang, Xiaojun; Han, Jiayi; Liu, Yatian; Hu, Jingwen; Li, Ming; Chen, Xi; Xu, Lin (Frontiers in Oncology, 2021)
Background: Esophageal squamous cell carcinoma (ESCC) is one of the most frequently diagnosed cancers in the world with a high mortality rate. The mechanism about ESCC development and whether miRNAs play a critical role remains unclear and needs carefully elucidated. Materials and Methods: high-throughput miRNA sequencing was used to compare the differential miRNAs between the ESCC tissues and paired adjacent normal tissues. Next, both CCK-8 and Transwell in vitro and xenograft mice model in vivo were used to testified the tumor-promoting effect of the selected miRNAs. In addition, we used bioinformatic tools to predict the potential target of the miRNAs and verified by Western Blot. Results: In ESCC, we identified two miRNAs, miR-17-5p and miR-4443, are stably up-regulated in ESCC tissues than adjacent normal tissues. The up-regulation of miR-17-5p and miR-4443 promote the tumor development in both in vitro and in vivo experiments. TIMP2 was proved to be the direct target of both of the miRNAs. And clinical ESCC tissues also showed down-regulation of TIMP2. Conclusions: This study highlights two oncomiRs, miR-17-5p and miR-4443, and its potential role in ESCC development by regulating TIMP2 expression, suggesting miR-17-5p and miR-4443 may serve as a novel molecular target for ESCC treatment.